2022
DOI: 10.1186/s13046-022-02319-z
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA-mediated DNA methylation: an emerging mechanism in cancer and beyond

Abstract: DNA methylation is one of the most important epigenetic mechanisms to regulate gene expression, which is highly dynamic during development and specifically maintained in somatic cells. Aberrant DNA methylation patterns are strongly associated with human diseases including cancer. How are the cell-specific DNA methylation patterns established or disturbed is a pivotal question in developmental biology and cancer epigenetics. Currently, compelling evidence has emerged that long non-coding RNA (lncRNA) mediates D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 142 publications
(125 reference statements)
2
59
0
Order By: Relevance
“…lncRNAs work mainly through the following four ways: first, induction, lncRNAs can bind to a specific miRNA, which can indirectly regulate the target gene; second, lncRNAs can act as a signal molecule on the pathway and regulate the upstream- and downstream-related genes of its target gene [ 31 , 32 ]. Third, by guiding the relevant RNA-binding proteins, lncRNAs are able to mediate the target genes via cis- or trans-regulation to specific protein complex sites [ 33 , 34 ]. Fourth, scaffolds, lncRNAs can be used as a platform; on this platform, a variety of related molecular complexes can be combined together to enhance the information transmission and interaction between molecular complexes [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs work mainly through the following four ways: first, induction, lncRNAs can bind to a specific miRNA, which can indirectly regulate the target gene; second, lncRNAs can act as a signal molecule on the pathway and regulate the upstream- and downstream-related genes of its target gene [ 31 , 32 ]. Third, by guiding the relevant RNA-binding proteins, lncRNAs are able to mediate the target genes via cis- or trans-regulation to specific protein complex sites [ 33 , 34 ]. Fourth, scaffolds, lncRNAs can be used as a platform; on this platform, a variety of related molecular complexes can be combined together to enhance the information transmission and interaction between molecular complexes [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our microarray analysis suggested that RARB was significantly upregulated in cells with DLEU2 knockdown and the subsequent qMSP assay identified increased DNA methylation at the RARB promoter. As aforementioned, lncRNAs may recruit, sequester, or regulate expression of DNMTs to regulate DNA methylation in downstream genes [ 15 ]. A recent publication by Zhang et al ., for instance, reported that lncRNA LALC recruits DNMTs to LZTS1 promoter to suppress its expression, which facilitated liver metastasis of CRC [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…DLEU2 has been associated with the proliferation and invasiveness of CRC cells [ 13 ], yet the possible molecules involved remain largely unknown. Intriguingly, certain lncRNAs may serve as manipulators for DNA methylation by regulating specific DNA methyltransferases (DNMTs) or Ten-eleven translocation family of enzymes [ 14 , 15 ]. DNA methylation refers to the selective methylation of cytosine within a cytosine-phosphate-guanine (CpG) dinucleotide, thus forming 5-methylcytosine [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are non-coding single-stranded RNAs with more than 200 nucleotides and have been found playing important roles in many biological processes in recent years. 12,13 LncRNA-H19 was one of the earliest lncRNAs to be discovered and has been increasingly recognized for its abilities to participate in cell function regulation, transcription and post transcriptional modification. 14,15 Our prior studies demonstrated that lncRNA-H19 regulated cell proliferation and invasion of ectopic endometrium by targeting ITGB3 via modulating miR-124-3p, 16 and it has also been reported that lncRNAs can be regulated by estrogen, 17,18 but it remains unclear whether estrogen regulates the expression and functions of lncRNA-H19 to participate in the pathogenesis of endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are non-coding single-stranded RNAs with more than 200 nucleotides and have been found playing important roles in many biological processes in recent years. 12 , 13 LncRNA-H19 was one of the earliest lncRNAs to be…”
Section: Introductionmentioning
confidence: 99%